Cellular Imaging of Inflammation after Experimental Spinal Cord Injury - Elizabeth A. Dunn; Lynne C. Weaver; Gregory A. Dekaban; Paula J. Foster (Molecular Imaging)
The ability to visualize the cellular inflammatory responses after experimental spinal cord injury (SCI) was investigated using a clinical 1.5-T magnetic resonance imaging scanner, a custom-built, high-strength gradient coil insert, a 3-D fast imaging employing steady-state acquisition (FIESTA) imaging sequence and a superparamagnetic iron oxide (SPIO) contrast agent. An “active labeling” approach was used, with SPIO administered intravenously at different time points following SCI. Our results show that this strategy can be used to visualize clusters of iron-labeled cells associated with the inflammatory response in SCI. Of particular importance for this application was the finding that in FIESTA images hemorrhage does not cause signal loss. In T2-weighted spin echo or T2*-weighted gradient-echo images, which are more commonly used to detect signal loss associated with SPIO, the signal loss associated with hemorrhage interferes with the detection of iron-induced signal loss. FIESTA, therefore, allowed us to discriminate between iron associated with blood products in hemorrhage that occurs in acute SCI and the iron associated with SPIO-labeled cells accumulating in the injured cord.